2020
DOI: 10.24036/108236-019883
|View full text |Cite
|
Sign up to set email alerts
|

Struktur, Diksi, Dan Konjungsi Teks Prosedur Karya Siswa Kelas Vii SMP Negeri 1 Kota Solok

Abstract: The research aims to describe generic structure and language features of procedure texts by seventh grade students in SMP Negeri 1 Kota Solok. The method that is used is descriptive qualitative method. The data of the research are procedure texts collected in many sources such as the documents of 32 text procedure written by the students. The instrument of this research is the researcher her self. Data were analyzed by describing, analyzing, and discussing the data toward the theory. Based on the results of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Diction is a form of word choice that is used appropriately and harmoniously in its use to express an idea to achieve the desired result [29]. The results of this study are relevant to previous research [30]. The research found some incorrect use of diction in the student's procedural text.…”
Section: Incorrect Use Of Dictionmentioning
confidence: 52%
“…Diction is a form of word choice that is used appropriately and harmoniously in its use to express an idea to achieve the desired result [29]. The results of this study are relevant to previous research [30]. The research found some incorrect use of diction in the student's procedural text.…”
Section: Incorrect Use Of Dictionmentioning
confidence: 52%
“…Selain itu, struktur dan kebahasaan dalam keterampilan menulis teks prosedur siswa masih bermasalah (Azura, 2017). Beberapa siswa belum mampu menulis teks prosedur karena belum memahami teks prosedur secara keseluruhan (Ulfa & Rasyid, 2019) dan diketahui juga bahwa siswa belum mencapai KKM dalam dalam menulis teks prosedur (Kadorin et al, 2017).…”
Section: Proses Pemajemukanunclassified
“…Wildani Ulfa (2019) pada penelitiannya di SMP Negeri 1 Kota Solok, menemukan permasalahan dalam keterampilan menulis yakni siswa masih kesulitan dalam menulis kalimat. Hal itu disebabkan karena siswa belum mampu memahami teks prosedur secara menyeluruh.…”
unclassified